BCL-2 and MYC gain/amplification is correlated with central nervous system involvement in diffuse large B cell lymphoma at leukemic phase. Issue 1 (December 2017) - Zou, Dehui; Yi, Shuhua; Cui, Rui; Liu, Wei; Li, Chengwen; Zhong, Shizhen; Yu, Zhen; Li, Zengjun; Lv, Rui; Ru, Kun; Wang, Huijun; An, Gang; et al.
Abstract Background Diffuse large B-cell lymphoma (DLBCL) of leukemic phase is a rare clinical manifestation, but is highly prevalent with central nervous system involvement (CNSI). Little is known about this rare clinical observation. Methods We reviewed the clinical characteristics of 40 DLBCL patients with leukemic phase identified by flow cytometry and analyzedBCL2 andMYC aberrations by fluorescence in situ hybridization. Results The median age of these 40 patients was 46 years (range, 15–75) with 19 men patients. All patients had bone marrow involvement, and fourteen (35.0%) had CNSI. There were respectively 14 patients (35.0%) had the BCL2 or MYC gain/amplification and nine of them (22.5%) simultaneously had both aberrations. Compared to those without CNSI, CNSI was found more commonly in male patients (71.4 vs. 34.6%, p  = 0.046), in those with IPI scores of 4–5 (57.1% vs. 11.5%, p  = 0.001), and in those with elevated serum LDH (100 vs. 61.5%, p  = 0.007) and both MYC and BCL2 rearrangement (88.9 vs. 19.4%;p  = 0.000). BCL2 and MYC rearrangements were the sole independent factor correlated with CNSI. Conclusion It is possible that both BCL2 and MYC gene aberrations may contribute to the high incidence of CNSI observed in leukemic phase of patients with DLBCL.